PENGEMBANGAN PRODUK GULA AREN CAIR HIGIENIS DAN INOVATIF DI DESA BANGKIR, KECAMATAN DAMPAL SELATAN - Satil Asmi; Mohammad Yahya; Desy Rahmawati; Fiansi Fiansi; Rian Christian Sondakh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Liquid palm sugar is a traditional product with high economic value that has the potential to be developed as a superior regional commodity. However, the main challenges faced are the still simple processing process and inadequate packaging, which impact the product's quality and shelf life. This research aims to develop liquid palm sugar with a hygienic processing process and innovative, more efficient, and environmentally friendly packaging. The methods used include filtration and pasteurization to maintain product quality, safety, and stability, and the use of environmentally friendly, airtight packaging to extend shelf life. The results show that the pasteurization process can reduce the number of contaminating microbes, thus extending the product's shelf life. The innovative packaging can maintain the flavor and physical quality of liquid palm sugar for several weeks longer than traditional packaging. Thus, the development of hygienic processing methods and innovative packaging not only improves the quality and shelf life of liquid palm sugar but also provides opportunities to increase product competitiveness in local and national markets.